Research Status of Home-Based Rehabilitation in Chronic Diseases and Construction of Intelligent Rehabilitation Treatment Platform - WANG Jinghua; YU Shaohong; LI Li (康复学报)
Chronic diseases seriously affect the health of residents in China and increase the burden on families and society. In China, the mortality rate caused by chronic diseases accounts for about 86% of the mortality rate of all related diseases, so as that the prevention and treatment situation is in a difficult situation. How to achieve real-time health monitoring and establish convenient and fast medical access to improve the quality of life in patients with chronic disease who live at home for a long time and have difficulty moving is the focus of chronic disease rehabilitation. Studies have shown that early identifications of changes in cardiopulmonary function in patients with chronic diseases is one of the ways for timely and effective rehabilitation intervention. In view of the development status of "Internet + medicine" and the practical needs of patients with chronic diseases, through reviewing and sorting out the relevant literature and materials on home-based rehabilitation of chronic diseases, the research trends of home-based rehabilitation of chronic diseases at home and abroad as well as the advantages and disadvantages of the current management modes were analyzed and summarized. On this footing, a closed-loop and full-cycle intelligent rehabilitation diagnosis and treatment platform for real-time monitoring, health guidance, online training and on-site diagnosis of health conditions of patients with chronic diseases at home could be constructed based on the monitoring of their cardiopulmonary function changes and supported by the network information center of tertiary hospitals. The diagnosis and treatment platform is a home-based intelligent and comprehensive rehabilitation comprehensive service platform which integrates service, management and operation and uses wearable devices, a network platform and mobile phone applications as media and utilizes variety of internet resources. By synchronizing data of the computer or mobile terminal platform, doctors and family members can grasp that the life, health, safety and other conditions of patients in time. A comprehensive rehabilitation service system for patients with chronic diseases featuring the interaction of doctors in tertiary hospitals, community doctors, patients and their families, including in-home, online and on-site services, could be constructed, and a bridge should be built between tertiary hospitals, community healthcare centers, home-based patients and medical insurance institutions to dynamically manage the health conditions of patients with chronic diseases. At the same time, the concept of traditional Chinese medicine (TCM) could be integrated to construct a new intelligent management model for home-based rehabilitation of chronic diseases, which is supposed to be an integration of TCM and Western medicine and a multidisciplinary approach, so as to provide decision-making reference for health management of chronic diseases in China.